A Critique on the Book Managerial Movements in Public Sector (Past, Present and Future) - Mehdi Golverdi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Public administration studies governments, government institutions, and structures, as well as the actions of individuals in the public sector. Numerous books have been written and translated in the field of public administration. Few of these books have gained legitimacy and acceptance among readers. The book Managerial Movements in Public Sector by Dr. Hasan Danaeefard is one of the most comprehensive books written in the field of public administration and therefore has been considered as a textbook for teaching in public administration courses and the main source of study for the graduate entrance exam for recent years. In this article, the attempt was to review the book in a descriptive-analytical manner, by mentioning the evidence and documents. The book was critiqued from four dimensions: formal, structure, writing and content. According to this, on one hand, the main strengths of the book are the use of credible sources, comprehensiveness and up-to-datedness of the content, accurate citation method, and use of practical examples. On the other hand, this book has also some drawbacks, the most important of which are lack of observance of writing symbols, inconsistency of some sentences, lack of image quality of the cover design and its incompatibility with the subject of the book and lack of structural and content coherence in some sentences.Keywords: